Hexagonal fractal ultra‐wideband antenna using Koch geometry with bandwidth enhancement. Issue 15 (1st December 2014) - Tripathi, Shrivishal; Mohan, Akhilesh; Yadav, Sandeep
Abstract : In this study, a design approach to achieve multiresonance phenomena in ultra‐wideband (UWB) bandwidth using fractal geometry is investigated. The introduction of Koch fractal geometry in monopole as well as in the ground plane of the antenna generates additional resonances, which helps to achieve entire UWB operational bandwidth. Therefore the bandwidth is increased up to 122%. Moreover, the fractal nature of the antenna also facilitates to obtain the stable radiation pattern. The compact dimension 31 mm × 28 mm of the antenna exhibits nearly omnidirectional radiation pattern, with good reflection coefficient over the entire UWB frequency range. The proposed prototype is fabricated and its measured results are in good agreement with the simulated one. The time‐domain analysis of the antenna is performed and it is found that fidelity factor is better than 0.81, which shows good pulse preserving capability of the antenna.